Vulnerability to simple faints is predicted by regional differences in brain anatomy - Beacher, Felix D.C.C. (Academic Press, 2009)
Neurocardiogenic syncope (NCS, simple fainting) is a common and typically benign familial condition, which rarely may result in traumatic injury or hypoxic convulsions. NCS is associated with emotional triggers, anxiety states and stress. However, the etiology of NCS, as a psychophysiological process, is poorly understood. We therefore investigated the relationship between NCS and brain anatomy. We studied a non-clinical sample of eighteen individuals with histories characteristic of NCS, and nineteen matched controls who had never fainted. We recorded fainting frequency, resting heart rate variability measures and anxiety levels. Structural T1-weighted magnetic resonance images (MRI) were acquired at 1.5 T. Associations between brain morphometry (regional gray and white matter volumes) and NCS, resting physiology and anxiety were tested using voxel-based morphometry (VBM). Compared to controls, NCS participants had lower regional brain volume within medulla and midbrain (a priori regions of interest). Moreover, across NCS individuals, lower gray matter volume in contiguous regions of left caudate nucleus predicted enhanced parasympathetic cardiac tone, fainting frequency and anxiety levels. Our findings provide preliminary evidence for a hierarchical anatomical basis to NCS. First, differences in the volume of brainstem centers supporting cardiovascular homeostasis may relate to constitutional predisposition to NCS. Second, differences in the structural organization of the caudate nucleus in NCS individuals may relate to fainting frequency via interactions between emotional state and parasympathetic control of the heart. These observations highlight the application of VBM to the identification of neurovisceral mechanisms relevant to psychosomatic medicine and the neuroscience of emotion.